Solitary posterior triangle neck mass as the rare sole presentation of papillary thyroid carcinoma (Bangladesh Journal of Otorhinolaryngology, 2012)
Introduction: Papillary thyroid carcinoma is the most common differentiated thyroid malignancy. It offers good prognosis and the presentation is usually consistent with an enlarged thyroid, mostly solitary nodule which biochemically euthyroid and radiologically normal appearance. On rare occasions, the thyroid gland enlargement can present together with multiple neck lymphadenopathy.Case report: We report a case of middle aged man presented with a posterior neck mass without any other symptom. Histopathology report of the excised mass confirmed the diagnosis of, papillary thyroid carcinoma which warranted total thyroidectomy and neck dissection.  DOI: http://dx.doi.org/10.3329/bjo.v18i1.10427 Bangladesh J Otorhinolaryngol 2012; 18(1): 87-90